Effect Of Environment Arrangement on Increasing Halal Tourism Visitors - Muflihatur Rohmah; Saif, Muhammad Burhan Abrori; Az-Dhifta Himmah Yasya (Journal of Islamic Economy and Community Engagement, 2022)
A healthy environment is an environment that has clean air, water and soil conditions and is free from pollution, and the area owned supports the creation of a healthy community. Automatically the environment will be protected from things that cause health problems, such as liquid, solid and gas waste. Also, avoid animals carrying disease germs, harmful chemicals, excessive noise pollution and other negative things. Conceptually, what can overcome environmental crises is to make eforts to preserve the environment by reforestation. The word preservation comes from "sustainable", which means to remain as it was before, not change, and last forever. At the same time, preservation means the process, method, act of preserving, protection from destruction and damage, preservation, conservation, and management of natural resources, which guarantees their wise use and the continuity of their supply while maintaining and increasing the quality, value and diversity. Environmental preservation is an effort to deal with problems that arise in an area. Therefore the 108 Thematic KKN Group 11 held environmental preservation, which applied the concept of greening by utilizing existing land around Halal Tourism belonging to the Islamic Boarding School, which is located on Jalan Wonosari KM 25 Dusun Joban, Beji Village, Patuk District, Special Region of Yogyakarta. This activity is a form of the community service program. The greening concept is carried out by planting several types of tree seeds by utilizing the land around the area. This greening activity is expected to raise a sense of community concern to always care for and care for the surrounding environment, in addition to providing skills and knowledge about making kokedama from coconut coir waste as a growing medium for ornamental plants.